Regeneration and reusability of anion exchange resin used in perfluorooctane sulfonate removal by batch experiments. Issue 2 (10th April 2013) - Chularueangaksorn, Pattarawan; Tanaka, Shuhei; Fujii, Shigeo; Kunacheva, Chinagarn
<x xml:space="preserve">Abstract</x> Perfluorooctane sulfonate (PFOS) has been increasingly considered an environmental micropollutant in recent years. The adsorption of PFOS by anion exchange resins and granular activated carbon was studied in this work. Additionally, the regeneration and reusability of the selected resin were further studied. The equilibrium adsorption data were fitted well by the Freundlich isotherm for all adsorbents. PFA300 had the highest adsorption capacity (455 mg/g) and the fastest adsorption rate. Regeneration studies of PFA300 were conducted using different types of regeneration solutions. The regeneration efficiency of PFA300 exceeded 99%. Regenerated PFA300 was reused as an adsorbent and showed high PFOS removal efficiency for six cycles. In this study, PFA300 had the highest adsorption capacity as well as good regeneration and reusability. Therefore, PFA300 is a promising adsorbent that can be used to remove PFOS in aqueous solution. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 884‐890, 2013